2017
DOI: 10.1007/jhep12(2017)098
|View full text |Cite
|
Sign up to set email alerts
|

One-loop QCD thermodynamics in a strong homogeneous and static magnetic field

Abstract: Abstract:We have studied how the equation of state of thermal QCD with two light flavors is modified in a strong magnetic field. We calculate the thermodynamic observables of hot QCD matter up to one-loop, where the magnetic field affects mainly the quark contribution and the gluon part is largely unaffected except for the softening of the screening mass. We have first calculated the pressure of a thermal QCD medium in a strong magnetic field, where the pressure at fixed temperature increases with the magnetic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…In recent years numerous activities have been in progress such as magnetic catalysis [1][2][3], inverse magnetic catalysis [4][5][6][7][8][9][10][11][12] and chiral magnetic effect [13][14][15] at finite temperature, and the chiral-and color-symmetry broken/restoration phase [16][17][18][19][20]. Also in progress is the study related to the equation of state (EoS) in thermal perturbative QCD (pQCD) models [21,22], holographic models [23,24] and various thermodynamic properties [19,20,25,26], refractive indices and decay constant of hadrons [27][28][29][30][31][32][33][34]; soft photon production from conformal anomaly [35,36] in HIC; modification of dispersion properties in a magnetized hot QED [37,38] and QCD [38][39][40][41] medium; and various transport coefficients [42]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years numerous activities have been in progress such as magnetic catalysis [1][2][3], inverse magnetic catalysis [4][5][6][7][8][9][10][11][12] and chiral magnetic effect [13][14][15] at finite temperature, and the chiral-and color-symmetry broken/restoration phase [16][17][18][19][20]. Also in progress is the study related to the equation of state (EoS) in thermal perturbative QCD (pQCD) models [21,22], holographic models [23,24] and various thermodynamic properties [19,20,25,26], refractive indices and decay constant of hadrons [27][28][29][30][31][32][33][34]; soft photon production from conformal anomaly [35,36] in HIC; modification of dispersion properties in a magnetized hot QED [37,38] and QCD [38][39][40][41] medium; and various transport coefficients [42]…”
Section: Introductionmentioning
confidence: 99%
“…Also using HTL approximation, some thermodynamic quantities in lowest Landau level (LLL) within the strong field approximation has been numerically computed in Ref. [22]. However, for the gluonic case, this calculation assumes that the only effect of the magnetic field is to shift the Debye mass without any change in the general structure of two point functions at the finite temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying physics of this phenomenon can only be a matter of conjecture. We may note, however, that it has been argued [41] that strong magnetic fields in the QGP (at LHC rather than RHIC impact energies) constrict the relevant phase space in a specific manner, and so tend to reduce the entropy density of the plasma. It may well be that some analogous mechanism is at work here, since vorticity and magnetic fields often have similar effects 12 .…”
Section: Resultsmentioning
confidence: 91%
“…Recently, several studies have found the effect of magnetic catalysis [8][9][10], i.e., the enhancement of phase transition temperature of QCD matter in presence of external magnetic field, whereas, some results of inverse magnetic catalysis [11][12][13][14][15][16][17][18] have been reported. Various properties of QCD matter at weak coupling in presence of magnetic field is being studied including the equation of state [19][20][21], transport properties [22][23][24]. Modification of QCD Debye mass and the two point correlation functions of quarks [25] and gluons [26][27][28] i.e., partons have been analyzed recently.…”
Section: Introductionmentioning
confidence: 99%